C-reactive protein increases myocardial damage after STEMI. (25th November 2020) - Garlichs, C.D; Ries, W; Torzewski, J; Pfluecke, C; Heigl, F; Darius, H; Ince, H; Mitzner, S; Nordbeck, P; Butter, C; Sheriff, A
Abstract: Background: The CAMI-1 study dealt with the depletion of CRP by apheresis in patients with acute myocardial infarction (AMI). CRP, the prototype human acute phase protein, has been known as a marker of poor prognosis in AMI and independently predicts 30-day mortality. Methods: 66 STEMI patients were enrolled in the study following complete coronary revascularization (2–12 h after the onset of symptoms). 32 patients received CRP apheresis, whereas 34 patients treated by standard protocols served as controls. CRP apheresis started 24±12 h and 48±12 h after onset of symptoms. In case of a rapid increase in CRP plasma levels following the 2nd session, a 3rd session was carried out another 24 h later. A specific CRP adsorber removed up to 79% of the original CRP. In each apheresis session, 6000 ml of plasma was treated via peripheral venous access. Primary study endpoint was myocardial infarction size as determined by Cardiac Magnetic Resonance Imaging (CMR) 2–9 days after STEMI. Results: Aphereses sessions were well tolerated with no relevant side effects. Peak CRP plasma levels after STEMI ranged from 9 to 279 mg/l. The expected peak CRP level after AMI can be calculated precisely with 2–3 CRP quantifications during the first 24 h after the onset of symptoms. The regression coefficient for this analysis is 0.91. This mathematical step allows for the comparison of the CRP-apheresis group and the controls on the basis of their individual CRP peak levels. The statistical evaluation shows that the CRP concentration is significantly associated with the damage (infarct size, LVEF, circumferential strain) in the controls. This association was lost in the aphereses patients: they performed significantly better at all endpoints (infarct size, LVEF, circumferential strain) than the controls. The CRP apheresis significantly reduced myocardial damage. To our surprise, two apheresis patients had an infarct size of 0%. Conclusions: For the first time we find an unequivocal association between myocardial infarct size and the CRP concentration. This is in some respects a surprise, since the basic assumption in AMI is that the vascular occlusion leads to primary damage and the reperfusion to secondary damage, which would not have led one to expect such a clear dose-response relationship as that observed here. In addition, our results show a significant beneficial effect of CRP apheresis on myocardial infarction size and wall motion. Selective CRP apheresis is now being further evaluated as a therapeutic approach in the treatment of acute myocardial infarction in a registry (CAMI registry). Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Pentracor GmbH